2020
DOI: 10.3390/microorganisms8040486
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Oil Modulates the Gut Microbiota Associated with Atherogenic Biomarkers

Abstract: During the last few decades there has been a staggering rise in human consumption of soybean-oil (SO). The microbiome and specific taxa composing it are dramatically affected by diet; specifically, by high-fat diets. Increasing evidence indicates the association between dysbiosis and health or disease state, including cardiovascular diseases (CVD) and atherosclerosis pathogenesis in human and animal models. To investigate the effects of high SO intake, C57BL/6 mice were orally supplemented with SO-based emulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Rechtman et al reported that supplementation of SO induced dysbiosis and that some bacterial taxa were positively correlated with the biomarkers of atherosclerosis. In their study, SO-based emulsion (SOE) was administered to C57B6 mice fed a chow diet for 4 weeks, and the SOE supplementation resulted in increases in the proportions of Bacteroidetes, Mucispirillum, Prevotella, and Ruminococcus, and decreased those of Firmicutes, when compared with the control group (Korach-Rechtman et al, 2020). On the other hand, Li et al compared the changes in the microbiota of rats fed a high-fat diet containing fish oil, lard, or SO at 4% (w/w) for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Rechtman et al reported that supplementation of SO induced dysbiosis and that some bacterial taxa were positively correlated with the biomarkers of atherosclerosis. In their study, SO-based emulsion (SOE) was administered to C57B6 mice fed a chow diet for 4 weeks, and the SOE supplementation resulted in increases in the proportions of Bacteroidetes, Mucispirillum, Prevotella, and Ruminococcus, and decreased those of Firmicutes, when compared with the control group (Korach-Rechtman et al, 2020). On the other hand, Li et al compared the changes in the microbiota of rats fed a high-fat diet containing fish oil, lard, or SO at 4% (w/w) for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation of soy macromolecules into short chain fatty acids (SCFAs) by probiotic bacteria is reported in fermented soy products from south east Asia. [18] SCFAs such as acetate and butyrate, [19] a major carbon source for colonocytes, can affect microbiota structure and act as anti-inflammatory immune modulators, [20,21] and are commonly produced by intestinal microflora and dairy starter cultures, including Lactobacilli sp. [22] Soy protein fractions, such as Bowman-Birk inhibitors (BBI) act as serine-protease inhibitors and have anti-inflammatory effects within the gastrointestinal system, as well as putative anticarcinogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ahsan (2018), soybeans are part of the legumes that comprise peanuts, chickpeas, other beans, and pulses, commonly processed into oil, flour, and meal. A large quantity of soybean oil is produced around the globe, making it one of the most common cooking oils available and is highly consumed across cultures (Deol et al, 2020;Korach-Rechtman et al, 2020). The oil is versatile and has been increasingly used in various cooking and industrial purposes (Cheng & Rosentrater, 2017).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%